Eksplorasi Penggunaan ChatGPT dalam Penulisan Artikel Pendidikan Matematika - edi supriyadi (Papanda Journal of Mathematics and Science Research, 2022)
This study aims to explore the potential of ChatGPT, an artificial intelligence platform developed by OpenAI, in assisting the process of writing research articles on mathematics education. This research is a qualitative descriptive study that collects a sample of data which is then checked using Turnitin to determine the plagiarism level of the contents of articles created by ChatGPT. Nonetheless, this study has limitations in the limited number of samples due to time and resource constraints. The purpose of this research is to find out how ChatGPT can help in the process of making math education research articles and whether it can improve the quality of the research articles that are made. The results of this research are expected to contribute to the latest studies on ChatGPT's ability to assist in the process of writing math education research articles, as well as provide input for teachers, lecturers, and other researchers in utilizing ChatGPT as a tool in the process of writing research articles